PROBLEMATIKA KESALAHAN BAHASA INDONESIA DALAM TATARAN SINTAKSIS - Deasy Supartini; Siti Solihah; Heri Isnaini (Institut Nalanda, 2023)
Indonesian has a special function in the midst of national and state life which is marked by the function of Indonesian as the state language and national language. In human life need communication and language. The communication that takes place can be verbal or written. These two forms of communication certainly require adequate language skills to produce an effective and efficient communication. Effectiveness and efficiency in speaking are strongly influenced by language skills. Especially skills in the preparation of sentences that will be used to communicate. The problems that occur in the Indonesian language are marked by language errors, especially the written language. Errors in the Indonesian language variety of writing are caused by various factors, including the construction of sentences which will start from an understanding of the meaning of the word as the constituent of the sentence, which will then form a phrase, clause, and in the end form a sentence to communicate so it is important to understand syntax as a a branch of linguistics or linguistics to be known by speakers of Indonesian so that communication becomes effective and efficient. Simply put, syntax can be interpreted as rules or principles in making sentences. Syntax is a branch of linguistics whose study includes the intricacies of grammar in sentence units. Quoted from the Big Indonesian Dictionary (KBBI) syntax has three meanings namely; (1) the arrangement and relationship of words with words or with other larger units (2) the branch of linguistics concerning the arrangement of sentences and their parts.